The Last Word - Pieter Fourie (Communicare)
WHERE DO WE STAND WITH THE “AFRICANISATION” OF COMMUNICATION STUDIES? As academics and lecturers we are well aware of the demands of transformation. Many of us have been and are going through the demanding, time-consuming and bureaucratic exercises of SAQAtising our syllabi. In the process, meaningless and unimaginative templates tend to dictate the academic activity, leaving little to the creative intellectual mind. We have been and are going through the processes of adapting our syllabi to outcome-based education and teaching, now to be turned into problem-solving education and teaching; of turning year courses into semester courses, and probably now converting them back to year courses; and of merging institutions and, in so doing, trying to marry different educational philosophies, practices, attitudes and organisational cultures. At Unisa, the above have been and are taxing experiences. Distance education demands that every word you utter has to go through a rigorous process of educational planning and design, writing, evaluation by critical readers, re-writting, re-evaluation, and proofreading over and again, before it goes through the processes of production and despatch. Now, a new phase of transformation has entered: the Africanisation of our courses. But what is Africanisation? The purpose of what follows is not to problematise and intellectualise the concept. That is done, more than often, in a stream of academic articles and in discussions among academics. The discussions usually begin with: “What the hell is Africanisation?” Neither is the purpose to deconstruct related concepts such as “conceptual engineering”, “cultural revolution”, “power”, “ideology”, “hegemony” and so on. Somewhere in the debate, they all feature. In the following paragraphs I prefer to quote verbatim, and in a paraphrased way, from two presentations given by two Unisa scholars at a seminar held on 3 March 2005 at Unisa on the topic of Africanisation. They are Prof. T.S. Maluleke, the Deputy Executive Dean of Unisa’s College of Human Sciences, and Prof. A.M.B. Mangu of Unisa’s Department of Constitutional, International and Indigenous Law. The purpose is not to comment on their presentations, but rather to uphold them as possible yardsticks against which to measure the resistance to, and/or progress or lack of progress in, the Africanisation of South African communication studies.